Normal "Abnormalities" in Palms - Timothy K. Broschat; Monica L. Elliott (EDIS)
ENH1077, a 7-page illustrated fact sheet by T. K. Broschat and M. L. Elliott, describes and illustrates some of these common "abnormalities" that cause concern among palm owners. Published by the UF Department of Environmental Horticulture, October 2007.